Chemical Composition of the Lumpy Bracket Mushroom (Trametes gibbosa) - Hossein Bakhshi Jouybari; Ahmadreza Bekhradnia; Fatemeh Mirzaee; Mohammad Hossein Hosseinzadeh; Emran Habibi* (Iranian Society of Pharmacognosy, 2022)
Background and objectives: Trametes species have been used for centuries in traditional medicine of Asian countries. Recently, some of the bioactive compound have been isolated and evaluated for therapeutic purposes from these species. The aim of this study was to report the isolation and structure elucidation of major sterols from fruiting bodies of Trametes gibbosa. Volatile compounds and antioxidant activities of the different mushroom extracts of mushroom were also examined. Methods: The fruiting bodies of T. gibbosa were extracted with n-hexane, methanol, and hot water, respectively. For isolation of sterols, the n-hexane extract was subjected to column chromatography and fractionated by step gradient of n-hexane: ethyl acetate. The volatile oil was prepared by hydrodistillation and analyzed by GC-MS. For evaluation of the antioxidant activity, 2,2-diphenyl-1-picrylhydrazyl and ferric reducing antioxidant power assays were used. Moreover, the phenolic and carbohydrate contents were assessed using spectrophotometry methods. Results: The column chromatography of the n-hexane extract led to the isolation of three sterols. These compounds were identified for the first time in T. gibbosa as follows: ergosta-5,7,22-trien-3β-ol (ergosterol); 5,8-epidioxy-ergosta-6,22-dien-3-ol; 5,9-epidioxy-8,14-epoxy-ergosta-6,22-dien-3-ol. The most abundant volatile compounds were identified as aldehydes (29.01%), fatty acids (21.2%) and alcohols (12.07%). Based on antioxidant results, methanol and hot water extracts showed the highest activities in DPPH (EC50=588.56±36.37 µg/mL) and FRAP (432±6.6 mmol Fe2+/g DW) methods, respectively. Conclusion: Trametes gibbosa is a valuable source of mycochemicals such as sterols, carbohydrate and phenolics. Further investigations are required for evaluation of the therapeutic potentials of the isolated compounds.